Transcriptome-wide study revealed m6A and miRNA regulation of embryonic breast muscle development in Wenchang chickens - Gu, Lihong; Jiang, Qicheng; Chen, Youyi; Zheng, Xinli; Zhou, Hailong; Xu, Tieshan (Frontiers in Veterinary Science, 2022)
N6-Methyladenosine (m6A) modification has been shown to play important roles in skeletal muscle development. Wenchang chickens are commonly used as a high-quality animal model in researching meat quality. However, there have been no previous reports regarding the profile of m6A and its function in embryonic breast muscle development of Wenchang chickens. In this paper, we identified different developmental stages of breast muscle in Wenchang chickens, and performed m6A sequencing and miRNA sequencing in the breast muscle of embryos. Embryo breast muscles, were weighed and stained with hematoxylin-eosin after hatching. We found that myofibers grew fastest at the 10th day after hatching (E10), and seldom proliferated beyond the 19th day after hatching (E19). A total of 6774 differentially methylated genes (DMGs) were identified between E10 and E19. For RNA-seq data, we found 5586 differentially expressed genes (DEGs). After overlapping DEGs and DMGs, we recorded 651 shared genes (DEMGs). Subsequently, we performed miRNA-seq analysis and obtained 495 differentially expressed miRNAs (DEMs). Then, we overlapped DEMGs and the target genes of DEMs and obtained 72 overlapped genes (called miRNA-m6A-genes in this study). GO and KEGG results showed DEMGs enriched in many muscle development related pathways. Furthermore, we chose WNT7B, a key regulator of skeletal muscle development, to perform IGV visualization analysis, and found that the m6A levels on the WNT7B gene between E10 and E19 were significantly different. In conclusion, we found that miRNAs, in conjunction with m6A modification, played a key role in embryonic breast muscle development of Wenchang chickens. The results of this paper offer a theoretical basis for the study of m6A function in muscle development and fat deposition of Wenchang chickens.